2022
DOI: 10.3389/fimmu.2022.829391
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Drug Release From Liposomes for the Remodeling of Systemic Immune Homeostasis and the Tumor Microenvironment

Abstract: Myeloid Derived Suppressor Cells (MDSCs) play important roles in constituting the immune suppressive environment promoting cancer development and progression. They are consisted of a heterogeneous population of immature myeloid cells including polymorphonuclear MDSC (PMN-MDSC) and monocytes MDSC (M-MDSC) that are found in both the systemic circulation and in the tumor microenvironment (TME). While previous studies had shown that all-trans retinoic acid (ATRA) could induce MDSC differentiation and maturation, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…It is interesting to observe that the nano-bowel structure covers only a part of the inner surface of liposomes. A similar phenomenon has been reported in previous study, where a poorly water soluble drug ( all-trans-retinoic acid) is actively loaded with calcium acetate gradient [ 53 ]. It is suggested that incorporation of hydrophobic drugs to the lipid bilayer can change its original ordered structure and fluidize the membrane [ 54 ].…”
Section: Resultssupporting
confidence: 86%
“…It is interesting to observe that the nano-bowel structure covers only a part of the inner surface of liposomes. A similar phenomenon has been reported in previous study, where a poorly water soluble drug ( all-trans-retinoic acid) is actively loaded with calcium acetate gradient [ 53 ]. It is suggested that incorporation of hydrophobic drugs to the lipid bilayer can change its original ordered structure and fluidize the membrane [ 54 ].…”
Section: Resultssupporting
confidence: 86%
“…The low-risk group with higher immune scores had smaller IC50 in 15 immunotherapeutic agents (Fig. 7B) [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and was more sensitive to 18 targeted therapeutics (e.g., Nilotinib) and six chemotherapeutic agents (e.g., Vinblastine) than the highrisk group. All 39 chemicals were shown in Fig.…”
Section: Clinical Treatment Response Analysesmentioning
confidence: 99%
“…148 Zheng et al investigated how a liposomal formulation of alltrans-retinoic acid (ATRA) can remodel the immunosuppressive TME by inducing MDSC differentiation and maturation. 159 They developed a sustained release formulation of actively loaded ATRA. Using a CT26 colon cancer mouse model, the authors found that liposomal ATRA alone, and in combination with immune checkpoint PD-1 inhibitors, significantly reduced tumor growth.…”
Section: Immunotherapymentioning
confidence: 99%
“…Using a 4T1 breast cancer mouse model, the authors found a time‐dependent accumulation of the formulation in the TME resulting in a synergistic immune response that was able to inhibit tumor growth in primary and spontaneously metastatic tumors as shown in Figure 7a–c 148 . Zheng et al investigated how a liposomal formulation of all‐trans‐retinoic acid (ATRA) can remodel the immunosuppressive TME by inducing MDSC differentiation and maturation 159 . They developed a sustained release formulation of actively loaded ATRA.…”
Section: Intravenous Delivery Of Lipid Nanoparticlesmentioning
confidence: 99%